2022
DOI: 10.1155/2022/9227790
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Solitaire FR Stent Thrombectomy Combined with the Suction Thrombus on the Clinical Effect and Prognosis of Acute Middle Cerebral Artery Occlusion

Abstract: To determine the curative effect and prognosis of Solitaire FR stent thrombectomy integrated with the suction thrombus on the treatment of acute middle cerebral artery occlusion (AMCAO). Based on the treatment, patients suffering from AMCAO were separated into the Solitaire FR group (Solitaire FR stent + suction thrombus) and suction group (suction thrombus). Modified thrombolysis in cerebral infarction grading, National Institutes of Health Stroke Scale (NIHSS) score, modified Rankin Scale score, and safety p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…An additional 2 studies were identified via expert recommendation. Finally, 10 studies with 6543 patients were determined to satisfy our inclusion criteria with the appropriate report of outcomes of interest (eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional 2 studies were identified via expert recommendation. Finally, 10 studies with 6543 patients were determined to satisfy our inclusion criteria with the appropriate report of outcomes of interest (eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 included studies, 8 studies used a retrospective design and 5 studies were multicenter studies. The size of the included studies ranged from 78 patients to 4169 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations